Analysis of Students' Mathematical Problem-Solving in Translating Story Problems into Mathematical Models - Nurjanah, Putri; Angraini, Lilis Marina (Progressive of Cognitive and Ability, 2024)
This study is driven by students' limited proficiency in converting narrative problems into mathematical representations. Additionally, a crucial facet of students' problem-solving skills involves their capacity to resolve mathematical problems. The primary objective of this research is to assess students' proficiency in solving mathematical problems by translating narrative scenarios related to linear equations of one variable into mathematical models. The research employed a descriptive qualitative approach. The participants comprised twenty-five eighth-grade students from a junior high school in Pekanbaru during the academic year 2023/2024. Data collection methods encompassed both test-based techniques employing mathematical problem-solving assessments and non-test methodologies involving interviews and documentation. The analysis involved data reduction, presentation, drawing conclusions, and verifying findings. From the study findings, it was evident that the students' proficiency in mathematical problem-solving yielded positive outcomes, averaging at 77.6%. Students' mathematical problem-solving ability in translating story problems into mathematical models with high ability has good mathematical solving ability characterized by students being able to master four or three problem-solving indicators. Students with medium ability have medium mathematical problem-solving ability which is characterized by students being able to master three or two problem-solving indicators. While students with low ability have low mathematical problem-solving ability which is characterized by students being able to two or one mathematical solving indicators.